Exploring the Linkage between Activity-Friendly Zoning, Inactivity, and Cancer Incidence in the United States - Nicholson, Lisa M. (Cancer Epidemiol Biomarkers Prev, 2017)
BACKGROUND: Physical activity (PA) protects against cancer and enhances cancer survivorship. Given high inactivity rates nationwide, population-level PA-facilitators are needed. Several authoritative bodies have recognized that zoning and planning helps create activity-friendly environments. This study examined the association between activity-friendly zoning, inactivity, and cancer in 478 of the most populous U.S. counties. METHODS: County geocodes linked county-level data: cancer incidence and smoking (State Cancer Profiles), inactivity (Behavioral Risk Factor Surveillance System), 11 zoning measures (compiled by the study team), and covariates (from the American Community Survey and NAVTEQ). For each zoning measure, single mediation regression models and Sobel tests examined whether activity-friendly zoning was associated with reduced cancer incidence, and whether inactivity mediated those associations. All models were clustered on state with robust standard errors and significance at the P<.05 level. RESULTS: Zoning for crosswalks, bike-pedestrian connectivity, and bike-pedestrian trails/paths were associated with reduced cancer incidence (β between −0.71 and −1.27, P<.05), about one case per 100,000 for each 10 percentage point increase in county population exposure to zoning. Except for crosswalks, each association was mediated by inactivity. However, county smoking attenuated these results, with only crosswalks remaining significant. Results were similar for males (with zoning for bike-pedestrian connectivity, street connectivity, and bike-pedestrian trails/paths), but not females, alone. CONCLUSION: Zoning can help to create activity-friendly environments that support decreased inactivity, and possibly reduced cancer incidence. IMPACT: Given low PA levels nationwide, cross-sectoral collaborations with urban planning can inform cancer prevention and public health efforts to decrease inactivity and cancer.